The Violent Surge: A Manifestation of Aggression - Akram, Muhammad; Javed, Amna; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
In theory, aggression is an unbridled and barbaric force—a violent manifestation of unbridled emotion. Think of it as an internal hurricane that is threatening to devour everything in its path due to its overwhelming force. It starts with a rising sensation of tension, an undercurrent that starts as a faint vibration under the surface, rather than a straightforward outburst of rage. Like the quiet before a storm, when the air crackles with possible peril, the energy is dark, deep, and menacing. Any sense of order is broken by the forms, which are twisted and jagged, with sharp and angular lines slicing through the room. These lines are unpredictable, scurrying in all directions, and some of them curve into tight spirals that symbolize the cyclical nature of violence, in which hostility feeds on itself, strengthening and developing until it becomes a force that sustains itself. They rip and tear at the surface, leaving the abstract terrain with deep, bleeding scars that stand in for both received and inflicted emotional traumas. The lines get sharper and more pointed, like daggers aiming to the soul's center, the more fierce the violence. Flashes of white-hot light, rays of vivid orange and bright yellow, pierce the darkness like abrupt explosions, contrasting with the starkness of the dark, aggressive tones. These flashes, which are short but incredibly bright, symbolize times of heightened anger when energy surges wildly, unleashing all that has built up in a violent outburst. They are a dazzling light of sheer intensity, full of unadulterated passion, rage, and strength, like flashes of heat in a frigid expanse. These brief but impactful moments, which are like explosions amid a sea of turmoil, leave their mark on the composition. This aggressiveness has a tangible texture that is rough and ripped apart by violent forces rather than smooth or clean. The heavy, rough brushstrokes give the impression that someone was painting frantically, disregarding accuracy in favor of impact. There isn't a smooth transition between colors and forms; instead, it seems like each component is vying for control of the image and never quite succeeding. Rather, they collide, overlap, and clash, which gives the piece a persistent sense of tension. The hostility itself seems uncontrollable, like a fire that burns in all directions at once, devouring everything in its path but never completely extinguishing.